2011
DOI: 10.1174/021037011794390085
|View full text |Cite
|
Sign up to set email alerts
|

Argument omissions in preschool Catalan and Spanish speaking children with SLI

Abstract: This paper describes three studies on verb production and argument structure in children with Specific Language Impairment (SLI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
17
0
5
Order By: Relevance
“…Children with SLI use significantly fewer argument types (Thordardottir and Weismer 2002) and omitted more grammatical subject arguments in ditransitive sentences than in sentences with intransitive and transitive verbs (Grela 2003). In this sense, a recent study of Catalan and Spanish children with SLI (Sanz‐Torrent et al 2011) describes three experiments on verb argument structure using different methodologies: an observational study which uses a spontaneous‐talk longitudinal sample, a sentence‐naming task as a result of event video observation and an experimental sentence‐naming task with static images that differ in the number of verb arguments. Although the specific results vary according to the methodology used, there was clear evidence that Catalan‐ and Spanish‐speaking children with SLI have special difficulties in producing verbs with a highly complex argument structure, often omitting obligatory arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Children with SLI use significantly fewer argument types (Thordardottir and Weismer 2002) and omitted more grammatical subject arguments in ditransitive sentences than in sentences with intransitive and transitive verbs (Grela 2003). In this sense, a recent study of Catalan and Spanish children with SLI (Sanz‐Torrent et al 2011) describes three experiments on verb argument structure using different methodologies: an observational study which uses a spontaneous‐talk longitudinal sample, a sentence‐naming task as a result of event video observation and an experimental sentence‐naming task with static images that differ in the number of verb arguments. Although the specific results vary according to the methodology used, there was clear evidence that Catalan‐ and Spanish‐speaking children with SLI have special difficulties in producing verbs with a highly complex argument structure, often omitting obligatory arguments.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments involving elicited sentences, Sanz-Torrent et al (2011) report similar patterns for Spanish–Catalin bilingual children with SLI. This type of error has also been found for other languages (Fletcher & Garman, 1988; de Jong, 1999; Schelletter et al, 1999).…”
Section: Discussionmentioning
confidence: 60%
“…Various studies (Grela & Leonard, 1997; de Jong, 1999; Loeb & Leonard, 1988; Schelletter, Sinka, Fletcher, & Ingham, 1999) have indicated that children with SLI have difficulties utilizing verb argument structure. A recent study of Catalan and Spanish children with SLI (Sanz-Torrent, Andreu, Badia, & Sidera, 2011) showed that Catalan- and Spanish-speaking children with SLI have special difficulties in producing verbs with a highly complex argument structure and make more mistakes in specifying obligatory arguments.…”
Section: Introductionmentioning
confidence: 99%
“…31, nº 3 (octubre) dad léxica que niños más pequeños con similar edad lingüís-tica (Leonard, Miller y Gerber, 1999) y que niños sin TEL de igual edad cronológica (McGregor, 1997); problemas en tareas de denominación (Lahey y Edwards, 1999;McGregor y Appel, 2002;McGregor, Rost, Guo y Sheng, 2010;Sheng y McGregor, 2010); limitaciones en la definición y búsqueda de sinónimos (Anglin, 1993;Mainela-Arnold, Evans y Coady, 2010;Marinelli y Johnson, 2002) y en la comprensión del significado verbal dentro del contexto gramatical (O'Hara y Johnston, 1997). Estudios realizados en idioma español han mostrado la pobre calidad en el uso de verbos en habla espontánea (Simon-Cereijido, 2009), limitaciones en la definición de palabras (Gutiérrez-Clellen y De Curtis, 1999), y un déficit general en el manejo de los verbos por una posible limitación en la representación mental (Andreu, Sanz-Torrent, Legaz y MacWhinney, 2012;Andreu, SanzTorrent, Olmos y MacWhinney, 2013;Sanz-Torrent, Andreu, Badia y Sidera, 2011).…”
unclassified
“…Se ha resaltado que es la pobreza lingüística la que provoca una escasa asertividad durante el proceso comunicación (Brinton, Fujiki y McKee, 1998). En español, las investigaciones han señalado la baja frecuencia de iniciativas conversacionales (Serra, 2002); una seria limitación en la comprensión de preguntas en las diferentes situaciones comunicativas (Monfort y Monfort, 2010); la comisión de errores gramaticales y de vocabulario en el discurso narrativo (Andreu et al, 2011) y la pobreza general de recursos semánticos en la formulación de expresiones comunicativas (Hincapie-Henao et al, 2008); los problemas para informar verbalmente con mensajes apropiados a la información visual (Katsos, Roqueta, Estevan, y Cummins, 2011) y para comprender el humor de los gráficos (Andrés, Clemente, Cuervo y Górriz, 2009); la incomprensión de intenciones comunicativas (Andrés-Roqueta y Clemente, 2010;Farmer, 2000;Gillott, Furniss y Walter, 2004) y de sentidos figurados o profundos del lenguaje (Andrés, Flores y Clemente, 2011).…”
unclassified